Family Migration Decisions - Mincer, Jacob (Journal of Political Economy, 1978)
This paper joins a few very recent attempts to analyze migration in the awareness of the family context. In contrast to most of them, my focus is exclusively on the family context. The paper defines family ties relevant to migration decisions and explains their effects on the probability of migration, on consequent changes in employment and earnings of family members, as well as on family integrity itself. Hopefully, the paper provides material for a missing chapter on family economics as well as an addition to the economics of labor supply arid of human capital formation.